User reactions to COVID-19 screening chatbots from reputable providers. (6th July 2020) - Dennis, Alan R; Kim, Antino; Rahimi, Mohammad; Ayabakan, Sezgin
Abstract: Objectives: The objective was to understand how people respond to coronavirus disease 2019 (COVID-19) screening chatbots. Materials and Methods: We conducted an online experiment with 371 participants who viewed a COVID-19 screening session between a hotline agent (chatbot or human) and a user with mild or severe symptoms. Results: The primary factor driving user response to screening hotlines (human or chatbot) is perceptions of the agent's ability. When ability is the same, users view chatbots no differently or more positively than human agents. The primary factor driving perceptions of ability is the user's trust in the hotline provider, with a slight negative bias against chatbots' ability. Asian individuals perceived higher ability and benevolence than did White individuals. Conclusions: Ensuring that COVID-19 screening chatbots provide high-quality service is critical but not sufficient for widespread adoption. The key is to emphasize the chatbot's ability and assure users that it delivers the same quality as human agents.